1997
DOI: 10.1046/j.1365-2168.1997.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of randomized controlled trials in laparoscopic surgery

Abstract: Readers should be cautious when interpreting the results of some of these trials and their impact on daily surgical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
1
27
1
1
Order By: Relevance
“…This relatively new diagnostic procedure which involves capturing a heavily T2 weighted image (which enhances fl uid containing structures) is rapidly gaining acceptance [12][13][14][15][16][17][18][19][20][21][22][23]. The reasons for this are (i) It is non-invasive (ii) It simultaneously gives considerable information regarding adjacent structures such as the pancreas and liver (iii) Allows for 3 dimensional reconstruction (iv) Combined with Gadolinium enhanced MR angiography forms a complete single investigation (v) Can replace intraoperative cholangiogram once experience at interpretation improves (vi) Shares the same disadvantages as ERCP in that it cannot differentiate between stone, sludge, mucus plugs…”
Section: Mrcp (Magnetic Resonance Cholangiopancreatogram)mentioning
confidence: 99%
See 2 more Smart Citations
“…This relatively new diagnostic procedure which involves capturing a heavily T2 weighted image (which enhances fl uid containing structures) is rapidly gaining acceptance [12][13][14][15][16][17][18][19][20][21][22][23]. The reasons for this are (i) It is non-invasive (ii) It simultaneously gives considerable information regarding adjacent structures such as the pancreas and liver (iii) Allows for 3 dimensional reconstruction (iv) Combined with Gadolinium enhanced MR angiography forms a complete single investigation (v) Can replace intraoperative cholangiogram once experience at interpretation improves (vi) Shares the same disadvantages as ERCP in that it cannot differentiate between stone, sludge, mucus plugs…”
Section: Mrcp (Magnetic Resonance Cholangiopancreatogram)mentioning
confidence: 99%
“…Choledocholithiasis can be diagnosed with a sensitivity of 88-92% and specifi city of 91-98% (vs. 98% for ERCP) [12][13][14][15][16][17][18][19][20][21][22][23]. In a blinded study with 110 patients, 30 with choledocholithiasis, 2 observers, one of whom had an experience of 2 years, achieved comparable results with a sensitivity of 90%, specifi city of 93%, positive predictive value of 82%, and negative predictive value of 96% and overall accuracy of 92% with inter-observer agreement of 93% [21].…”
Section: Mrcp (Magnetic Resonance Cholangiopancreatogram)mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The current (over) enthusiasm for minimally invasive surgery should be tempered by the realization that several trials have failed to demonstrate much benefit for laparoscopic cholecystectomy over small incision surgery [10]. Slim and his colleagues analysed reports of published RCTs in laparoscopic surgery and showed that the majority of these trials were poorly designed, did not address appropriate end points and used inadequate sample sizes [11]. It is not inconceivable that later RCTs may throw up nasty surprises for surgeons who are doing many presently popular procedures without adequate evidence.…”
Section: The Era Of Evidence Based Practicementioning
confidence: 99%
“…3 Few surgical RCTs report and justify sample size calculations, and insufficient study power is one of the major shortcomings of many surgical trials. 4 For example, systematic reviews of the surgical RCTs have shown that only 28% of coronary artery bypass grafting surgery trials, 4 12% of trauma or orthopedic surgery trials, 5 41% of pancreatico-duodenectomy trials 6 and 25% of laparoscopic surgery trials 7 have reported sample size calculations. The findings from underpowered and poorly designed surgical RCTs may be overvalued because their design grants them unwarranted credibility.…”
mentioning
confidence: 99%